Cristianismo e Mandato Cultural. Uma Análise Bíblica e Histórico teológica de Modelos de Comprensão da Relação entre Fé Cristã e Cultura - Schwambach, Claus (Vox Scripturae - Revista Teológica Internacional, 2011)
The present article covers in a first instant the theological references that determine a Christian vision of what is “culture”. In a second moment, the question of the relation between general revelation and specific revelation is worked in a biblical and historical perspective, in its implications to the comprehension of the cultural mandate. In a third moment, it´s looked at the relation between the post-modern macro-ecumenism and the cultural mandate, searching in macro-ecumenism´s comprehension models for understanding the cultural mandate. At the end, the author presents a conclusive reflexion about what he understands for a Christian comprehension of “culture”.